Fractional singular Sturm-Liouville operator for Coulomb potential - Bas, Erdal; Metin, Funda (Springer, 2013)
In this paper, we define a fractional singular Sturm-Liouville operator having Coulomb potential of type A/x. Our main issue is to investigate the spectral properties for the operator. Furthermore, we prove new results according to the fractional singular Sturm-Liouville problem.
Keywords: fractional; Sturm-Liouville; Caputo; Coulomb; singular; spectral